Saint young men. 1 - Nakamura, Hikaru, 1984- (Kodansha Comics, 2019)
"Jesus, the Son of God. Buddha, the enlightened one. Two of history's most important figures whose sagely deeds have been told and retold. After a few millennia of helping humanity, they have decided to take some time off and rent an apartment together in modern-day Tokyo. But even their saintly status hasn't fully prepared them to navigate the ups and downs of life in 21st century Japan, from theme parks, to shopping for rice cookers, to the wonderful world of manga. Follow this pair on a goofy, light-hearted, and pun-filled adventure in friendship."--